2006
DOI: 10.1096/fj.06-6152fje
|View full text |Cite
|
Sign up to set email alerts
|

A noncanonical SH3 domain binding motif links BK channels to the actin cytoskeleton via the SH3 adapter cortactin

Abstract: Calcium-activated potassium (BK) channels play a central role in regulating multiple physiological processes, from the control of blood flow to neuronal excitability. Coordinated regulation of BK channel activity by changes in actin cytoskeleton dynamics has been implicated in several of these processes and related disease states such as epilepsy and stroke. However, how BK channels interact with the actin cytoskeleton is essentially unknown. Here we demonstrate noncanonical Src homology domain 3 (SH3) binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 63 publications
(108 reference statements)
2
82
1
Order By: Relevance
“…Intron 16 immediately precedes an exon that codes for the nonconserved region linking the Ca 2ϩ -sensing RCK1 and RCK2 domains. Within the proline-rich sequence encoded in this exon, a noncanonical Src homology domain 3 (SH3) is expressed which allows BK Ca channels to coordinate their spatial distribution within the actin cytoskeleton through the actin adapator protein cortactin (40). In the i16-containing mRNA knockdown experiments, we observed a radically different distribution where the BK Ca channel protein was far less likely to colocalize with filamentous actin in dendritic spines.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Intron 16 immediately precedes an exon that codes for the nonconserved region linking the Ca 2ϩ -sensing RCK1 and RCK2 domains. Within the proline-rich sequence encoded in this exon, a noncanonical Src homology domain 3 (SH3) is expressed which allows BK Ca channels to coordinate their spatial distribution within the actin cytoskeleton through the actin adapator protein cortactin (40). In the i16-containing mRNA knockdown experiments, we observed a radically different distribution where the BK Ca channel protein was far less likely to colocalize with filamentous actin in dendritic spines.…”
Section: Discussionmentioning
confidence: 88%
“…In the i16-containing mRNA knockdown experiments, we observed a radically different distribution where the BK Ca channel protein was far less likely to colocalize with filamentous actin in dendritic spines. Changes in BK Ca channels firing properties are synchronized with alterations in actin cytoskeletal dynamics (41) in some forms of stroke and epilepsy (40). One obvious question is to what extent neurons use an i16-containing mRNA to generate a functional BK Ca channel that can properly coordinate with the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…More sequences have been identified, including cortactin SH3 binding RxxPxxxP found in the cytoplasmic region of the calcium activated potassium (BK) channel (Tian et al 2006) and FUS1 binding Arg-Ser-rich sequences (Tong et al 2002). Two new sequences have been found for Saccharomyces cerevisiae actin binding protein involved in the organization of actin cytoskeleton Abp1p-SH3, +PX (P/V/L)XXPX + and PXXPXRPXW(L/I).…”
Section: Specificity Of Bindingmentioning
confidence: 99%
“…Tian et al (140) demonstrated interactions between the COOH-terminal poreforming ␣-subunit of BK Ca channels and cortactin, which created bridges with the cortical actin cytoskeleton. Moreover, the actin-cortactin-BK Ca channel complex was shown to regulate BK Ca channel activity (140). Similarly, cortactin was found to interact with K v 1.2 channels and to modulate their function and trafficking in HEK-293 cells (161).…”
Section: Mechanisms Responsible For Control Of Cell Migration/prolifementioning
confidence: 99%